2018
DOI: 10.1007/s00394-018-1820-0
|View full text |Cite
|
Sign up to set email alerts
|

Substitution of red meat with poultry or fish and risk of type 2 diabetes: a Danish cohort study

Abstract: Replacing processed red meat with poultry, replacing total or processed red meat with fish, and replacing processed red meat with unprocessed red meat were all associated with a lower risk of type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…Yet another surprising finding is that the effect of red meat is independent of animal fat or its most common saturated fatty acid, palmitic acid. The takehome message of the study is consistent with that of a recent report that fish intake relative to red meat, lowers the risk of type 2 diabetes, yet another chronic disease (11). Interestingly, with type 2 diabetes, poultry consumption showed protective effects not noted with endometriosis.…”
supporting
confidence: 88%
“…Yet another surprising finding is that the effect of red meat is independent of animal fat or its most common saturated fatty acid, palmitic acid. The takehome message of the study is consistent with that of a recent report that fish intake relative to red meat, lowers the risk of type 2 diabetes, yet another chronic disease (11). Interestingly, with type 2 diabetes, poultry consumption showed protective effects not noted with endometriosis.…”
supporting
confidence: 88%
“…In 2010, a meta-analysis documented 19% higher diabetes risk per 50 g/day PRM, while URM does not reach significance [28]. Additionally, a study reported that replacing PRM with UPM reduced T2DM incidence (HR 0.96, 95% CI 0.93, 0.99) [51]. Factors which might help to explain the higher RR for PRM include higher saturated fatty acid, sodium, heme iron, and salt content [28,52,53], the aromatic hydrocarbons, heterocyclic amines and Advanced Glycation End Products (AGEs) that arise from hightemperature making-processing [54,55] and the nitrates-nitrites preservatives added in processing [52].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, rich in total fat, saturated fat and other potential nutritional components (41,42) , red meat may independently or synergistically interact with heme iron to affect glucose metabolism. Poultry and fish are health substitutions of red meat and processed meat to help decrease the risk of developing T2DM (43) . Red meat, especially fresh fatty pork, is the main component of total meat intake in China (44) , red meat was close to 76% of total meat in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, rich in total fat, saturated fat and other potential nutritional components (41,42) , red meat may independently or synergistically interact with haem Fe to affect glucose metabolism. Poultry and fish are health substitutions of red meat and processed meat to help decrease the risk of developing T2DM (43) .…”
Section: Discussionmentioning
confidence: 99%